Pengelolaan Air Tanah dalam Perspektif Global: Review Artikel atas Tantangan Polusi dan Perubahan Iklim - Ahmad Zainuri; Nurdin Mohamad; Marini Susanti Hamidun; Sukirman Rahim; Abdul Haris Panai (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Groundwater plays a crucial role in supporting ecosystems and meeting human needs, but increasing human activities and climate change threaten its sustainability. In the Murray-Darling Basin, Australia, and South Africa, climate change exacerbates groundwater depletion, reducing river flows and damaging ecosystems. Governance challenges and groundwater pollution from industrial and agricultural activities are also significant, as seen in the Netherlands and Uzbekistan. Studies indicate regulatory gaps and the need for more advanced predictive models, such as 3D models to monitor saltwater intrusion in Vanuatu. These findings highlight the necessity of integrated policies, governance reforms, and technological innovation for sustainable groundwater management. The implications stress the importance of long-term planning to address nitrogen pollution and excessive groundwater extraction to safeguard this vital resource for future generations.